The Canadian Light Source : a story of scientific collaboration - Bancroft, G. M. (George Michael); Johnson, D. D. (Dennis Duane) 1938- (University of Toronto Press, 2020)
"The creation of the Canadian Light Source in Saskatoon, which began operation in 2004, was the largest science project in Canada in the last fifty years. The multi-beam facility operates over five thousand hours per year for over one thousand Canadian and international users from a wide range of science, medical and engineering disciplines. This book describes the decades of intense research from many scientists to justify this project; the remarkable and unprecedented collaboration and cooperation of governments, universities, and industries across Canada; and the resulting outstanding research covering many areas of the physical, biological, medical, and agricultural sciences. With personal accounts and frank narration, this book describes the long history from 1934-2001 leading to the CLS, beginning in Saskatoon in the 1930s. The major part of the book details the remarkable and unselfish collaboration and cooperation of a few hundred people from Canadian and international universities, governments, and industry, showcasing how the Canadian Light Source represents pure and applied research at its finest."--